Features of the Concept of "Anger" in English and Uzbek Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article examines the features of the concept “anger” in English and Uzbek languages. The purpose of the work is to systematically describe interlingual similarities and differences in the conceptualization of emotions using the material of the Uzbek and English languages, and in each cluster the bulk of linguistic means expressing different aspects of emotions are analyzed. It turns out that given the presence of numerous semantic contrasts between individual words in the Uzbek and English languages, as well as the frequent absence of an unconditional translation equivalent, the structure of emotional clusters largely overlaps.